PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP EFFECTIVE TAX RATE (ETR) (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2013) (Students' Journal of Accounting and Banking, 2015)
This research investigates the influence of good corporate governance influences Effective Tax Rate (ETR). Good corporate governance are measured by the audit committee, institusional ownership, number board of commissioner, and percentage of independent commissioner. This research sample is manufactured company registered on the Stock Exchange during the year 2011-2013 by using of method purposive sampling. There are 154 companies fulfilling criterions. This research used multiple regression analysis. The results of this research indicates that institusional ownership affect Effective Tax Rate (ETR) significantly. Meanwhile, the proportion of independent commissioners, the number board of commissioner does not significantly influence the company's Effective Tax Rate (ETR). Keywords: Good Corporate Governance, Effective Tax Rate (ETR), The Audit Committee, and Institusional Ownership, Board of Commissioner, and Independent Commissioner